2022
DOI: 10.1007/1345_2022_167
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Length of Day and El-Niño Using Wavelet Coherence Method

Abstract: The relationship between the length of day (LOD) and El-Niño Southern Oscillation (ENSO) has been well studied since the 1980s. LOD is the negative time-derivative of UT1-UTC, which is directly proportional to Earth Rotation Angle (ERA), one of the Earth Orientation Parameters (EOP). The EOP can be determined using Very Long Baseline Interferometry (VLBI), which is a space geodetic technique. In addition, satellite techniques such as the Global Navigation Satellite System (GNSS), Satellite Laser Ranging (SLR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is shown that oceanic angular momentum (OAM), hydrological angular momentum (HAM), and sea level angular momentum (SLAM) can have a nonnegligible effect on polar motion and dUT1 as well (Bizouard & Seoane, 2010; Brzezinski & Nastula, 2002; Chin et al., 2004; Dahlen, 1976; Dill & Dobslaw, 2010; Dobslaw et al., 2010; Gross, 2008; Kiani Shahvandi, Schartner, & Soja, 2022; Luo et al., 2022; Nastula & Ponte, 1999). Furthermore, phenomena such as El Niño Southern Oscillation (ENSO) can have some influence on the rate of dUT1 (Raut et al., 2022; Xu et al., 2022). This can be analyzed using climatic indices (CIs) like the multivariate ENSO index (MEI, Wolter & Timlin, 1993), the Madden Julian Oscillation index (MJI, Kiladis et al., 2014), and the North Atlantic Oscillation index (NAI, Visbeck et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that oceanic angular momentum (OAM), hydrological angular momentum (HAM), and sea level angular momentum (SLAM) can have a nonnegligible effect on polar motion and dUT1 as well (Bizouard & Seoane, 2010; Brzezinski & Nastula, 2002; Chin et al., 2004; Dahlen, 1976; Dill & Dobslaw, 2010; Dobslaw et al., 2010; Gross, 2008; Kiani Shahvandi, Schartner, & Soja, 2022; Luo et al., 2022; Nastula & Ponte, 1999). Furthermore, phenomena such as El Niño Southern Oscillation (ENSO) can have some influence on the rate of dUT1 (Raut et al., 2022; Xu et al., 2022). This can be analyzed using climatic indices (CIs) like the multivariate ENSO index (MEI, Wolter & Timlin, 1993), the Madden Julian Oscillation index (MJI, Kiladis et al., 2014), and the North Atlantic Oscillation index (NAI, Visbeck et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The LOD is the most challenging parameter to forecast since the greatest difficulties come from the occurrence of extreme events such as El Nino, which have demonstrated themselves in LOD signals [ 7 , 8 , 9 ]. The changes in the LOD could be due to tidal or non-tidal origins.…”
Section: Introductionmentioning
confidence: 99%